The characterization of outer membrane vesicles (OMVs) and their role in mediating antibiotic-resistance gene transfer through natural transformation in Riemerella anatipestifer - Mengying Wang; Yizhou Yao; Yuhao Yang; Dekang Zhu; Mingshu Wang; Renyong Jia; Shun Chen; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; Juan Huang; et al. (Poultry Science, 2025)
Riemerella anatipestifer (R. anatipestifer, RA) is the etiological agent of duck serositis, an acute multisystemic disease in ducks that is globally distributed and causes serious economic losses in the duck industry. Despite exhibiting multidrug resistance, the transmission mechanism of its antibiotic resistance genes (ARGs) remains incompletely identified. To contribute to addressing this gap, in this study, outer membrane vesicles (OMVs) from the RA strain CH-1 were isolated and characterized to investigate their involvement in ARG transfer in RA. Sequencing and data analysis revealed that RA CH-1 OMVs had ∼2.04 Mb genomic size, representing 88.3 % of the RA CH-1 genomic length. Proteomic analysis showed that OMVs contained 577 proteins, representing 27.2 % of the bacterial proteins. Subsequent investigations demonstrated that OMVs from antibiotic-resistant strains transferred ARG fragments and plasmids to the sensitive strain RA ATCC11845, relying on the natural transformation system, and the transformants exhibited corresponding resistance. Overall, OMV-mediated horizontal transfer of ARGs serving as a significant mechanism for acquiring multiple resistance genes in R. anatipestifer.